Acarbose is as effective as metformin in reducing central obesity in infertile women with polycystic ovary syndrome - Islam, Tahmida; Akter, Asma; Laila, Rawnok; Renu, Rafikunnahar; Khatun, Sumyara; Ishrat, Shakeela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Polycystic ovary syndrome (PCOS) in infertile women is frequently associated with insulin resistance and obesity. Optimization of the patient by reducing weight and insulin resistance improves clinical, biochemical & endocrine parameters and consequently increases the chance of successful ovulation and pregnancy. Acarbose is an alpha-glucosidase inhibitor which acts by reducing and slowing down intestinal absorption of glucose, with a reduction of the postprandial glucose wave and a consequent reduction of insulin secretion. The objective of this study was to evaluate the efficacy of acarbose compared to metformin, in reducing central obesity in infertile women with PCOS. Methods: This randomized controlled trial study was conducted on a total 60 infertile, overweight and obese women with PCOS. The women were allocated randomly to two treatment arms: one group receiving acarbose 100 mg three times daily with meal for 3 months and another group receiving metformin 500 mg three times daily after meal for 3 months. The main outcome variables were changes in central obesity and insulin resistance. Results: Mean weight, BMI, waist circumference and waist hip ratio was significantly decreased in both acarbose and metformin group. Reduction of fasting blood sugar, fasting insulin and HOMA-IR were also significant. The reduction was more in acarbose group, but the difference was not statistically significant. Gastrointestinal side effects were more in the women given metformin. Conclusion: There is significant reduction in central obesity or insulin resistance parameters in infertile PCOS women given acarbose or metformin over three months. However, there is no statistically significant difference between the two groups. Acarbose has less gastrointestinal side effects, so can be a suitable alternative to metformin in those who are intolerant to metformin.